KINERJA KEUANGAN TERHADAP KEMAMPUAN BERKELANJUTAN PERUSAHAAN - Kurnia Octha Saputri (JRAK, 2019)
This study aims to investigate the financial performance and sustainable company ability and investigate the effect of financial performance as measured by by profitability (ROA), capital adequacy (CAR), operational performance efficiency (BOPO), liquidity (FDR), and non performing financing (NPF), on the sustainable company ability as measured by the FSR at Sharia Commercial Bank in Indonesia for the period 2012-2016.The sample used in this research is 11 Sharia Commercial Banks. The sample selection technique used is purposive sampling. Methods of data analysis using panel data regression analysis with 5% significance. The result of t test shows that capital adequacy has significant positive effect, meanwhile profitability operational performance efficiency, liquidity, and non performing financing has significant negative effect. The result of F test shows that simultaneously the financial performance has significant effect on corporate sustainable capability with adjusted R2 of 0.581292.